Common carp aquaculture Cyprinus carpio in Iraq: history, challenges, and opportunities - Ali AL-Hilali, Hasan; R. Lozovskiy, Alexander (Indonesian Society of Scientific Aquaculture (ISSA), 2026)
Common carp (Cyprinus carpio) is a cornerstone of freshwater aquaculture in Iraq, playing a vital role in food security, rural livelihood, and economic development. This article provides a comprehensive overview of the historical introduction and evolution of carp farming in Iraq, highlighting its adaptability to diverse environmental conditions and its integration into various aquaculture systems, such as pond and cage culture. The study examines the economic significance of carp production, particularly in rural areas, where it serves as a primary source of income and animal protein. It also explores the challenges faced by the sector, such as water scarcity, disease outbreaks, and environmental impacts, while emphasizing the importance of sustainable practices and technological advancements. The article underscores the potential for future growth through genetic improvement, integrated farming systems, and government support in line with global sustainability goals. By addressing these challenges and leveraging opportunities, Iraq’s carp aquaculture sector can enhance productivity, ensure food security, and contribute to the nation’s economic resilience. Keywords: carp production, food security, polyculture systems Abstrak Ikan mas (Cyprinus carpio) merupakan komponen utama dalam akuakultur air tawar di Irak, memainkan peran penting dalam ketahanan pangan, mata pencaharian pedesaan, dan pembangunan ekonomi. Artikel ini memberikan gambaran komprehensif mengenai pengenalan sejarah dan perkembangan budidaya ikan mas di Irak, menyoroti adaptabilitasnya terhadap berbagai kondisi lingkungan, serta integrasinya ke dalam berbagai sistem akuakultur seperti budidaya di kolam dan keramba. Penelitian ini juga mengkaji signifikansi ekonomi produksi ikan mas, khususnya di daerah pedesaan, di mana ikan mas berfungsi sebagai sumber utama pendapatan dan protein hewani. Selain itu, artikel ini mengeksplorasi tantangan yang dihadapi sektor ini, seperti kekurangan air, wabah penyakit, dan dampak lingkungan, sembari menekankan pentingnya praktik berkelanjutan dan kemajuan teknologi. Artikel ini juga menyoroti potensi pertumbuhan di masa depan melalui perbaikan genetik, sistem pertanian terintegrasi, dan dukungan pemerintah sesuai dengan tujuan keberlanjutan global. Dengan mengatasi tantangan ini dan memanfaatkan peluang yang ada, sektor akuakultur ikan mas di Irak dapat meningkatkan produktivitas, memastikan ketahanan pangan, dan berkontribusi pada ketahanan ekonomi negara. Kata Kunci: ketahanan pangan, produksi ikan mas, sistem polikultur